The effectiveness of the financial intelligence unit in Maldives in combating money laundering / Ahmed Jaleel ... [et al.] - Jaleel, Ahmed; Syed Mustapha Nazri, Sharifah Nazatul Faiza; Zolkaflil, Salwa; Omar, Normah; Shafie, Nur Aima (Universiti Teknologi MARA, 2021)
Money laundering has become a vast global concern, and the rates are growing. Hence, there is a need for a good preventive and monitoring mechanism that monitors suspicious transactions at the source. In Maldives, a Financial Intelligence Unit (FIU) was introduced to gather, analyse, and provide financial intelligence report to law enforcement agencies to proceed with an investigation. The FIU plays a vital role in the Anti-Money Laundering (AML) Regime in successfully combat money laundering activities. Since the AML Regime in Maldives was established in 2014, there is a need to conduct a study to investigate the effectiveness of the FIU in combating money laundering in the Maldives. Based on questionnaires collected from 122 enforcement officers, findings show that reporting mechanisms significantly influence the effectiveness of the FIU. The legal framework and the role of the officer did not significantly influence the effectiveness of FIU. It shows that the competency of LEAs in combating money laundering in the Maldives is still low. Therefore, the government needs to enhance the awareness and competencies of enforcement officers in combating money laundering. Future research may conduct a comparative study to understand further the best reporting mechanism that can help enhance the effectiveness of law enforcement agencies.